Glucose Tolerance - Chackrewarthy, Sureka (IntechOpen, 2012)
The progression from normal glucose tolerance (NGT) to type 2 diabetes involves intermediate stages of impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), also known as prediabetes. The pathophysiology underlying the development of these glucose metabolic alterations is multifactorial, leading to an alteration in the balance between insulin sensitivity and insulin secretion. Our knowledge of the molecular basis of the signaling pathways mediating the various physiologic effects of insulin is steadily advancing. New substrates and signaling molecules have been identified and potential mechanisms involved in the pathophysiology of type 2 diabetes have been revealed. This book summarises the current state of knowledge on the pathophysiology underlying the progression from normal glucose tolerance to type 2 diabetes and therapeutic advances in the improvement of glycaemic control in prediabetic and diabetic states.